2 - Rethinking the Humanities in CODESRIA’s Programmes - Senkoro, F.E.M.K. (CODESRIA Bulletin, 2021)
Debate: The Humanities in the CODESRIA Project From 28 to 29 August 2015, CODESRIA held a planning meeting in Accra, Ghana in collaboration with the University of Ghana to deliberate on the location of the humanities in the life and work of a social science organisation like CODESRIA. The think pieces featured in this section emanated from the meeting.